2022
DOI: 10.1111/1471-0528.17115
|View full text |Cite
|
Sign up to set email alerts
|

Middle cerebral arterial flow redistribution is an indicator for intrauterine fetal compromise in late pregnancy in low‐resource settings: A prospective cohort study

Abstract: We aimed to determine the prevalence of abnormal umbilical artery (UA), uterine artery (UtA), middle cerebral artery (MCA) and cerebroplacental ratio (CPR) Doppler, and their relationship with adverse perinatal outcomes in women undergoing routine antenatal care in the third trimester.Design: Prospective cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Our results showing that a low CPR is associated with an increased risk of SNM are consistent with previous publications, demonstrating that the CPR is associated with a range of poor perinatal outcomes such as acidosis, intrapartum fetal compromise, admission to the NICU, stillbirth and adverse neurological sequelae in childhood 29–32 . Our findings of a lack of significant association between a low CPR and PNM after adjustment for confounders are in keeping with a large prospective study published in 2019 17 that demonstrated that although a low CPR was associated with adverse perinatal outcome (defined as a composite of stillbirth, neonatal death or HIE), the addition of the CPR contributed little in regard to prediction of adverse outcomes over and above that determined by maternal demographics and medical history.…”
Section: Discussionsupporting
confidence: 92%
“…Our results showing that a low CPR is associated with an increased risk of SNM are consistent with previous publications, demonstrating that the CPR is associated with a range of poor perinatal outcomes such as acidosis, intrapartum fetal compromise, admission to the NICU, stillbirth and adverse neurological sequelae in childhood 29–32 . Our findings of a lack of significant association between a low CPR and PNM after adjustment for confounders are in keeping with a large prospective study published in 2019 17 that demonstrated that although a low CPR was associated with adverse perinatal outcome (defined as a composite of stillbirth, neonatal death or HIE), the addition of the CPR contributed little in regard to prediction of adverse outcomes over and above that determined by maternal demographics and medical history.…”
Section: Discussionsupporting
confidence: 92%
“…Perinatal and maternal outcomes were assessed at the time of birth and up to 28 days postnatally. Additional information on the EPID study is published elsewhere [12][13][14] . All women recruited to the main prospective cohort provided informed and written consent, with illiterate participants signing using a thumbprint.…”
Section: Design and Participantsmentioning
confidence: 99%
“…Although such strategies or their evidence base are often lacking in LMICs, there is some evidence about possible low‐cost diagnostic approaches to assess fetal risk following reduced FM: for example, measuring maternal blood pressure, fetal heart rate and fundal height, 13 or antenatal (handheld) ultrasound to detect and monitor high‐risk pregnancies. Measuring fetal blood flow in Doppler ultrasound studies has also been useful, particularly in detecting growth restriction 6,14 . Involving women and health workers in studies will ensure the consideration of health‐system constraints and allow these to be embedded in the design, implementation and evaluation of any new intervention.…”
mentioning
confidence: 99%
“…Measuring fetal blood flow in Doppler ultrasound studies has also been useful, particularly in detecting growth restriction. 6 , 14 Involving women and health workers in studies will ensure the consideration of health‐system constraints and allow these to be embedded in the design, implementation and evaluation of any new intervention. If proven effective, this will increase the chance of the seamless integration of the intervention into existing care, and positive perceptions by providers and pregnant women, and will not increase the burden on already overwhelmed healthcare workers.…”
mentioning
confidence: 99%